2002
DOI: 10.1053/rapm.2002.29123
|View full text |Cite
|
Sign up to set email alerts
|

Infraclavicular block with lateral approach and nerve stimulation: Extent of anesthesia and adverse effects

Abstract: Single injection infraclavicular block, using a vertical paracoracoid approach, appears suitable for surgery distal to the elbow. Selective anesthesia of the medial cutaneous nerve is useful in improving tolerance of the tourniquet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0
6

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 19 publications
2
40
0
6
Order By: Relevance
“…Topical local anesthetic application in association with chosen regional anesthetic technique decreases tourniquet pain [66]. In brachial plexus block, anesthesia of the medial cutaneous nerves by a skin infiltration of local anesthetic at the root of the arm improved arm tourniquet tolerance [67]. Other factors such as tourniquet size, inflation pressure, and duration impact on patient discomfort [68][69][70][71].…”
Section: Recommendation Ementioning
confidence: 99%
“…Topical local anesthetic application in association with chosen regional anesthetic technique decreases tourniquet pain [66]. In brachial plexus block, anesthesia of the medial cutaneous nerves by a skin infiltration of local anesthetic at the root of the arm improved arm tourniquet tolerance [67]. Other factors such as tourniquet size, inflation pressure, and duration impact on patient discomfort [68][69][70][71].…”
Section: Recommendation Ementioning
confidence: 99%
“…Vascular puncture may lead to complications during an infraclavicular brachial plexus block [7]. From retrospective ultrasound imaging of this patient, the axillary vein coursed in the potential path of the anesthetic needle (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…However, the Horner's syndrome remains rare and even absent in some large infraclavicular block series [7]. Jandard et al [8] observed 4 cases of Horner's syndrome out of 100 patients undergoing a single paracoracoid vertical approach. Furthermore, Kilka et al [9] reported a Horner's syndrome rate of 7% using a distinct infraclavicular vertical technique in 175 patients.…”
Section: Discussionmentioning
confidence: 99%